Exile and embrace : contemporary religious discourse on the death penalty in America - Santoro, Anthony R., 1939- (Boston : Northeastern University Press, 2013)
"With passion and precision, Exile and Embrace examines the key elements of the religious debates over capital punishment and shows how they reflect the values and self-understandings of contemporary Americans. Santoro demonstrates that capital punishment has relatively little to do with the perpetrators and much more to do with those who would impose the punishment. Because of this, he convincingly argues, we should focus our attention not on the perpetrators and victims, as is typically the case in debates pro and con about the death penalty, but on ourselves and on the mechanisms that we use to impose or oppose the death penalty"--Provided by publisher.
Introduction -- Between moral certainty and morally certain : the churches discuss the death penalty -- Between the innocent man and Osama bin Laden : the believer and the death penalty, as viewed from the pew -- The exile : instantiated and revealed -- The bloggers' exegesis : from the death penalty to taxonomies of the executive -- Death, difference, and conscience -- Opening the space : from exile to embrace -- Conclusion.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Capital punishment -- United States -- Religious aspects; RELIGION -- Christian Life -- Social Issues; RELIGION -- Christianity -- General; Capital punishment -- Religious aspects; United States; Electronic books; Electronic books